2016
DOI: 10.4137/bcbcr.s40358
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Awareness and Prevention Behavior among Women of Delhi, India: Identifying Barriers to Early Detection

Abstract: BACKGROUNDGlobally, breast cancer (BC) has become the leading cause of mortality in women. Awareness and early detection can curb the growing burden of BC and are the first step in the battle against BC. The aim of this qualitative study was to explore the awareness and perceived barriers concerning the early detection of BC.METHODSA total of 20 focus group discussions (FGDs) were conducted during May 2013–March 2014. Pre-existing themes were used to conduct FGDs; each FGD group consisted of an average of ~10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
1
25
0
3
Order By: Relevance
“…A qualitative study on challenges to cancer treatment in India identified cultural values and stigma as key barriers to treatment [ 10 ], while a qualitative study in Thailand found that women faced social stigma and isolation following breast cancer treatment [ 25 ]. Another qualitative study conducted in India found that social stigma as a result of believing breast health problems were a reflection of poor character contributed to hiding breast cancer symptoms [ 26 ]. Furthermore, the link between cervical cancer and the human papillomavirus, a common sexually transmitted infection, has further stigmatized this disease in some places [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study on challenges to cancer treatment in India identified cultural values and stigma as key barriers to treatment [ 10 ], while a qualitative study in Thailand found that women faced social stigma and isolation following breast cancer treatment [ 25 ]. Another qualitative study conducted in India found that social stigma as a result of believing breast health problems were a reflection of poor character contributed to hiding breast cancer symptoms [ 26 ]. Furthermore, the link between cervical cancer and the human papillomavirus, a common sexually transmitted infection, has further stigmatized this disease in some places [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in concordance with that of the women in this study, who affirmed that marriage prospects for them and their family members would be at stake if they were detected with a lump. Some studies have reported 'cost' 'shyness' and 'fear' among other factors as barriers to screening (Lyttle and Stadelman, 2006;Dey et al, 2016). These were echoed by our participants as well, who expressed fear of impending costs of treatment, embarrassment and social stigma as factors that prevented them from accessing screening services.…”
Section: Discussionmentioning
confidence: 51%
“…These were echoed by our participants as well, who expressed fear of impending costs of treatment, embarrassment and social stigma as factors that prevented them from accessing screening services. The study by Dey et al, (2016) reported that being diagnosed with a breast anomaly amounted to the woman being branded as immoral, which in turn prevented her from seeking help. This fortunately did not seem to be a concern among women in this region and this probably is a reflection of the relatively higher education and living standard that this southern Indian province boasts of ("Udupi District Human Development Report -2014Report - ," 2014.…”
Section: Discussionmentioning
confidence: 99%
“…74 Individual-and societal-level social barriers for breast cancer in Indian women include cancer stigma, fear, fatalism and financial constraint. 76 Global evidence shows the importance of health-systems constraints for women's cancers related to development of health services, availability of health insurance, distance to cancer services as well as gender equity and human development. 77 Thus, sociocultural barriers to cancer control are key challenges in India.…”
Section: Public Health Implicationsmentioning
confidence: 99%